2019
DOI: 10.3390/md17030161
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification of Carotenoid-Producing Rhodotorula sp. from Marine Environment and Optimization for Carotenoid Production

Abstract: Carotenoids are natural pigments found in plants and microorganisms. These important nutrients play significant roles in animal health. In contrast to plant production, the advantages of microbial fermentation of carotenoids are the lower media costs, fast growth rate of microorganisms, and the ease of culture condition control. In this study, a colony of red pigment-producing yeast, Rhodotorula sp. RY1801, was isolated from the sediment of marine environment with the potential to produce carotenoids. Optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 32 publications
(34 reference statements)
4
48
0
Order By: Relevance
“…Similarly, the optimum temperature for either biomass or carotenoid production by Rhodotorula sp. RY1801 was 28 • C when glucose was used as a carbon source [47]. Another study investigating the effect of different temperature degrees on Sporobolomyces ruberrimus carotenoid using glycerol as a carbon source, the result revealed that the carotenoid production occurred whenever the temperature was kept between 19 • C and 27 • C, but at 31 • C the cells remained colorless, and no pigment production was seen [48].…”
Section: Microscopic Examination Of R Glutinis Cellular Shapes and Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the optimum temperature for either biomass or carotenoid production by Rhodotorula sp. RY1801 was 28 • C when glucose was used as a carbon source [47]. Another study investigating the effect of different temperature degrees on Sporobolomyces ruberrimus carotenoid using glycerol as a carbon source, the result revealed that the carotenoid production occurred whenever the temperature was kept between 19 • C and 27 • C, but at 31 • C the cells remained colorless, and no pigment production was seen [48].…”
Section: Microscopic Examination Of R Glutinis Cellular Shapes and Lmentioning
confidence: 99%
“…These data indicated the role of phosphate to enhance the efficiency of glucose uptake from the growth media by the studied yeast strain and its further conversion to either biomass or carotenoid. Although several studies were conducted to study the effect of different culture condition on carotenoid production by red yeasts [29,45,47,[55][56][57][58], as far as is known, there is no study that investigated the effect of phosphate on carotenoid production by red oleaginous yeast until now. A similar study conducted on algae [59] reported that both growth, chlorophyll, and beta carotene were significantly enhanced with increasing phosphorus concentration in the growth medium of Dunaliella salina.…”
Section: Microscopic Examination Of R Glutinis Cellular Shapes and Lmentioning
confidence: 99%
“…Currently, carotenoid-producing yeasts are mainly represented by the genera Rhodosporidium , Xanthophylomyces Rodotorula and Sporobomyces . The latter genus has a close relationship to the genus Sporidiobolus and represents the main source of torulene and torularhodin [ 32 ]. The quantity of total carotenoids produced by S. ruineniae A45.2 was in the range of those produced by the yeast studied in previously published reports [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of bacterial carotenoid was calculated by measuring the absorbance (at 480 nm) of carotenoid suspension and then using this value in the formula together with conversion factors. The below equation was used to calculate carotenoid yield and concentration, where A is absorbance (at 480 nm), D is dilution factor, V is solvent volume (mL) and W is bacteria dry weight (g) (Gu et al, 2008;Carvalho et al, 2012;Zhao et al, 2019).…”
Section: Cultivation Of R Sphaeroides In Bioreactor and Total Carotementioning
confidence: 99%